The influence of implementing Discovery Learning Model and giving motivation on students’ learning outcomes in Islamic education subject - Shilfia Alfitry (Nalar: Journal of Pedagogy and Society, 2020)
This study aims to solve initial problem on students’ low learning outcomes for Islamic religious education subject. The data analysis technique of this study used a regression analysis method. Based on the results of the analysis, the effect of implementing the discovery learning model to the students’ learning outcomes shows that t-test result is greater than t-table both at the significant level of 5% and the significant level of 1% (2,000 <14,242> 2,660). It means that Ha is accepted and H0 is rejected. Then, the effect of giving motivation by teachers on the students’ learning outcomes also shows that t-test result is greater than t-table both at the significant level of 5% and the significant level of 1% (2,000 <14,336> 2,660). It can be inffered that Ha is accepted and H0 is rejected. The data analysis on the influence of both implementing discovery learning model and giving motivation by the teacher on the student learning outcomes results show a significant level at the 5% significance level and 1% significance level (2,000 <5.576> 2.660). It can be concluded that implementing discovery learning model and giving motivation by teacher have a positive influence to help the students in achieving the learning outcomes.